(untitled) (Praxis Educativa, 2018)
Conceiving the curriculum as an element in which different knowledge and interests et inside the game, in this paper, we propose a compilation of background records that have addressed curricular change and, while analyzing some of them, we propose a particular way of approaching to the analysis of this process taking into account current research. The precedents are located mainly in universities in Rio de la Plata countries and analyze the change from two spotlights: subjects and products. The comprehension of these processes would be enriched if the institutional and disciplinary logics that operate in the change were considered, at least in undergraduate programs of certain areas of knowledge.